Toote vyadon ka untoota ithihas: Bhartyia rajya aur adivasi log - Sharma, B. D. (New Delhi, 2010)
This poignant powerful text provides an unerring archive of the cruel history of broken promises and needs to be read word by word from the dedication page to the last page.This book combines extra-ordinary scholarship on the economic, political, administrative and legal aspects fused together in probably the best available historical narrative on tribal question in post-independence India.
Keywords: Tribes and tribals-India